2000
DOI: 10.1128/jvi.74.4.1973-1984.2000
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Murine Gammaherpesvirus 68 M1 Open Reading Frame Leads to Enhanced Reactivation from Latency

Abstract: The gammaherpesviruses include the human pathogens Epstein-Barr virus (EBV) and Kaposi's sarcoma-associated herpesvirus (KSHV, or HHV-8) (for review, see references 10 and 18). These viruses establish lifelong infection of the host and are associated with a number of malignancies. To better understand gammaherpesvirus pathogenesis, we and others have begun to utilize infection of mice with murine gammaherpesvirus 68 (␥HV68, also referred to as MHV-68) (23, 37). ␥HV68 is a member of the gamma 2 -herpesvirus sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
139
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(150 citation statements)
references
References 36 publications
10
139
1
Order By: Relevance
“…Bacterial artificial chromosome derived wild-type MCMV (strain K181-Perth) and MHV68 WUMS [obtained from American Type Culture Collection (ATCC) #VR1465] were generated on NIH 3T3 fibroblasts (ATCC, #CRL-1658) as previously described (39,40). Viral stocks were propagated, clarified, and concentrated as previously described (41).…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial artificial chromosome derived wild-type MCMV (strain K181-Perth) and MHV68 WUMS [obtained from American Type Culture Collection (ATCC) #VR1465] were generated on NIH 3T3 fibroblasts (ATCC, #CRL-1658) as previously described (39,40). Viral stocks were propagated, clarified, and concentrated as previously described (41).…”
Section: Methodsmentioning
confidence: 99%
“…HHV8 (or KSHV, Kaposi's sarcoma associated herpesvirus) as well as the animal g-herpesviruses, herpesvirus Saimiri (a squirrel herpesvirus), MHV68 (murine g-herpesvirus 68), and EHV2 (equine herpesvirus-2) all encode chemokines and/or chemokine receptors and many members cause fulminate lymphomas and other neoplasias in the haemopoietic system of their hosts. Animal models of herpesvirus Saimiri and MHV68, including genetically modi®ed virus (Clambey et al, 2000), have contributed to a greater understanding of the immunology and virological aspects of g-herpesvirus pathogenesis, since these viruses are able to establish both acute and persistent infection in laboratory mice (Simas and Efstathiou, 1998;Jung et al, 1999). These studies have shown that during the acute phase, virus replication is detected in multiple organs, whereas latency is mainly restricted to B-lymphocytes and macrophages.…”
Section: Virally Encoded Chemokines and Chemokine Receptorsmentioning
confidence: 99%
“…with 10 5 PFU of wild-type ␥HV68 (29), ␥HV68-open reading frame (ORF) 72 mutant (27), ␥HV68-M1 mutant (M1-LacZ and M1-␦511) (30), and ␥HV68-M1 marker rescue (␥HV68-M1-MR) (30) in 0.5 ml of DMEM. Virus stocks were grown and quantitated as previously described (27,30). Animals received humane care and treatment in accordance with institutional guidelines.…”
Section: Mice and Viral Infectionmentioning
confidence: 99%